América Latina en la internacional comunista 1919-1943. : diccionario biografico - Jeifets, Lazar (CLACSO, 2017)
The Latin American Council of Social Sciences (CLACSO) is pleased to present the third corrected and enlarged edition of the work Latin America and the Communist International, 1919-1943. Biographical dictionary, prepared by Lazar Jeifets and Víctor Jeifets from the autobiographical notes kept in the old archive of the Communist International (today REGASPI) and other sources, thanks to its open access, to an intense collaborative dialogue of multiple people who have made grow this essential work since its first edition in Russian seventeen years ago and its publication in 2004 in Spanish. This monumental full effort in solidarity is an important contribution to academic research and critical thinking, which strengthens the academic internationalization processes in Latin America and the Caribbean through the subject itself. This Biographical Dictionary allows us, first of all, to approach multiple stories of struggle in Latin America. From these notes, which lead us to learn about those relentless combats at the hands of their own protagonists, a little-known Latin America emerges, that of those men and women who, under their own and different conditions, embraced a common cause, as internationalists, against oppression, injustice, misery and exploitation.